Autonomy in Extremis: An Intelligent Waiver of Appeals on Death Row - Johnson, Robert (American journal of criminal justice, 2014)
This article provides an in-depth account of the experiences of one condemned prisoner, Joseph Mitchel Parsons, who made the profound decision to waive his appeals and expedite his execution after serving eleven years under sentence of death in the State of Utah. Parsons determined that, at best, he faced years of appeals culminating in a long or life sentence that would likely end in a slow death in prison by unknown causes. Dropping his appeals, in contrast, offered a quick death in the execution chamber on a timetable under his control. The court granted Parsons the right to drop his appeals and expedite his execution. We provide evidence from this case study that the court allowed Parsons to make an autonomous decision to die on his own terms. As this research illustrates, an evaluation of the voluntariness of decisions to waive appeals in capital cases must be nested in an understanding of the death row experience of the individual under study. Case studies of the death row experience of those who waive their appeals, such as the research reported here, are integral to understanding these momentous decisions.